EXAMINATION OF IN VITRO WOUND HEALING ANTIMICROBIAL ACTIVITY OF EXTRACT OF SELECTED MEDICINAL PLANTS - T, CHANDUKISHORE; D, SAMSKRATHI; TL, SRUJANA (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The objective of this study was to discover and examine the in vitro wound healing activity of selected medicinal plants against common wound infecting microorganisms. Methods: Ziziphus rugosa and Hemidesmus indicus plant parts were used for aqueous and solvent extract preparation, maceration technique was followed. In vitro antibiotic test has been done using disc diffusion method. Results: Maximum yield for aqueous extract was observed in Z. rugosa bark sample (50.6%) and minimum yield was noted in H. indicus leaf extract in (45.7%) and maximum yield in solvent extract was observed in methanol extract of Z. rugosa (37.5%) whereas minimum yield was observed in of acetone extract of leaves of Z. rugosa (25%). For all sample extracts tested, leaf extract of acetone and methanol extract of Z. rugosa and H. indicus showed the highest antibiotic zone of inhibition of 15 mm and 12 mm, whereas lowest zone of inhibition was observed in aqueous bark extract of Z. rugosa (7 mm). Conclusion: Crude aqueous and solvent extract of selected plant were showed that promising results have a wound healing aid, efficacy of which could be further improved by studying and practicing more advanced extraction procedure for future prospectus.